Molecular Characterization of Calamus guruba and Calamus gracilis for their Genetic Diversity and Phyiogeny - Dutt, Garima; Raj, Hans; Sharma, Pratibha; Meena, Rajendra K.; Bhandari, Maneesh S.; Kant, Rama; Meena, Rajendra K. (Indian Forester, 2020)
Two rattan species Calamus guruba and C. gracilis of Mizoram were taken up for molecular characterization through inter simple sequence repeat (ISSR) markers. A total of 235 bands were generated in both the species when subjected to PCR amplification with 10 ISSR primers and all were found polymorphic across the species. As per the ISSR calculated value of various diversity measures, gene diversity recorded in C. guruba (percentage ofpolymorphic bands, P% = 65.11%; Shannon’s Information indices, I = 0.247) and C. gracilis (P% = 57.02%; I = 0.228) were lesser than other rattan species. As the sampled populations belonged to two different species, high level of variation was observed among the species (45%) which resulted in greatergenetic differentiation (PhiPT = 0.453 and GST: 0.261) andless gene flow (Nm = 1.416). Genetic distinctness was also shown by the presence of large number of private bands in both the species. Also the genotypes of both the species were grouped into two distinct clusters in dendrogram generated with un-weighted pairgroup method with arithmetic averages (UPGMA) and plot ofprincipal coordinate analysis (PCoA). The analysis of molecular variance revealed that 55% of the variation exists within the species and 45% between the species. Based upon the field observation and data generated here in, it is recommended that the natural populations are reduced and marked with lower genetic diversity, and therefore required suitable conservation measures.